Lignolytic Enzymes (Laccase and Peroxidase) production by Pink Oyster Mushroom, Pleurotus djamor - Toppo, Swati Rose (Mushroom Research, 2021)
This research work attempts the use of biogas digester liquid (BDL) as an inducer for lignolytic enzyme activity by Pleurotus djamor when grown in SSF culture condition. BDL rich in polyphenols and micronutrients can induce lignin degrading enzymes such as laccase and peroxidase.Â  Spraying 100 ml BDL/bag (1kg paddy straw)/day was found to increase yields of Pleurotus djamor in SSF and also reduced the time for various stages of mushroom growth such as pin head formation, fruiting body formation and first flush by 3-5d.Â  Of the 100ml BDL sprayed 70ml was collected as leachate and this showed highlignolytic enzyme (Laccase 150 U/L and Peroxidase 160U/L) activities in SSF and the enzyme activity coincided with the specific mushroom growth stages.